THE MISSIONARY WOMEN IN THE INLAND OF AUSTRALIA AND THE AUSTRALIAN INLAND MISSION AS REPRESENTED IN BETH BECKETT'S LIFE MEMOIR - Eliyanah, Evi (TEFLIN Journal, 2015)
This article looks at the gender dimension of religious missions administered by the Presbyterian Church in the inland Australia as represented in Beth Beckett's life memoir written in 1947-1955. It is aimed at obtaining general ideas on the involvement of women, as the wives of missionaries, Focusing on the experience of Beth Beckett, it argues that her position as a wife of a missionary is problematic: on the one hand she did transgress the traditional idea of staying home wife by choosing to travel along with her husband, but at the same time, she was still bound by the domestic side of the job.